Evaluation and Strengthening Recommendations of Rectorate Building Muhammadiyah University of Sumatra Barat Due to Earthquake - Habirun, Asiya Nurhasanah; Kurniawan, Deddy; Ad'ha, Muhammad Fajri (Semesta Teknika, 2024)
The UM Sumbar Rectorate building suffered structural damage after 33 years. During service life, earthquakes have frequently occurred, the largest was 7.6 magnitude earthquake 2009 in Padang. The structural components have never been handled. This study aims to identify the existing condition as a basis for handling structural damage. Research activities are structure inspection, structural analysis, and determining structural improvements. The building has been deflected by 1° (± 10cm). The majority of structural elements are cracked due to overcapacity. Based on ATC 40 pushover analysis results, it found that 10 steps on x-direction and 11 steps on y-direction of push loads on the structure until it collapsed. Structure performance level is Life Safety, which is in a plastic condition. Strengthening are suggested to increasing column, building ductility, and implementing a dilation system. Evaluation the foundation structure and soil investigation are necessary before planning the strengthening.